DNA damage, mutations and aging 2 - Vijg, Jan (Henry Stewart Talks, 2017)
Measuring somatic mutations in humans, How to detect mutations in normal cells, genome-wide, in humans?, If DNA damage and mutations drive aging, why is the germline immortal?